The personality of highly trained athletes in view of the big five model - Krol-Zielinska, M.; Ciekot-Soltysiak, M.; Zielinski, J.; Kusy, K. (Journal of Kinesiology and Exercise Sciences, 2016)
Study aim. The aim of the study was to examine the basic personality traits of athletes practicing sports disciplines of a different type of physical effort and training (high-speed, endurance and mixed) at a master level and to present the basic structures of behavior associated with the resulting personality profile. Materials and Methods. The study included 47 athletes aged 23.5 ± 4.2 years, representing Poland at international competitions: 11 sprinters, 15 endurance sports athletes (triathletes and long-distance runners), 14 futsal players and 7 Olympic taekwondo athletes. In order to study the personality of the athletes, we used a Polish adaptation of the NEO-FFI questionnaire. Results. Highly-trained sprinters, triathlonists, long-distance runners, futsal players and taekwondo athletes did not differ significantly from each other in terms of personality traits. However, all of the athletes were characterized by a high level of conscientiousness, statistically higher compared with those from the standardization group. Sprinters, endurance athletes and futsal players demonstrated a significantly lower level on the scale of openness to experience compared to those from the standardization group. Endurance athletes and futsal players were characterized by lower levels of neuroticism and higher extraversion. Conclusions. High-class athletes differ from the general population in terms of personality traits, which is why it is necessary to know their individual psychological characteristics in order to optimize training.